1995
DOI: 10.1002/art.1780380410
|View full text |Cite
|
Sign up to set email alerts
|

Increased proteoglycan synthesis in cartilage in experimental canine osteoarthritis does not reflect a permanent change in chondrocyte phenotype

Abstract: Objective. To determine whether chondrocytes in early experimental osteoarthritic (OA) cartilage continue to show increased synthesis and turnover of proteoglycans (PGs) during explant culture. A comparison was also made between the responsiveness of experimental OA and control cartilage to interleukin-lf3 (IL-1p) and tumor necrosis factor a (TNFa) after 1 day and 3 days in culture.Methods. OA was induced in mature animals by sectioning of the anterior cruciate ligament followed by 3 months of normal exercise.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Nevertheless, our present data are consistent with the occurrence of a hypertrophic response that initially compensates for the direct suppression of matrix synthesis due to IL-1␤. This is consistent with the increase in cartilage matrix synthesis that is seen in the early stages of OA (28)(29)(30).…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, our present data are consistent with the occurrence of a hypertrophic response that initially compensates for the direct suppression of matrix synthesis due to IL-1␤. This is consistent with the increase in cartilage matrix synthesis that is seen in the early stages of OA (28)(29)(30).…”
Section: Discussionsupporting
confidence: 84%
“…These authors indicated that this alternative treatment might not fully promote Ven et al 20 explained that the release of TGF-β may be caused by excessive compression to the joint and loosening of the collagen, which is quite likely to occur in early osteoarthritis. The effects of this growth factor depend on various situations such as whether the TGF-β receptors are in their active or latent form, expression of TGF-β receptors, and the presence of mutations that do not allow correct protein transduction, resulting in deficiency of TGF-β.…”
Section: Discussionmentioning
confidence: 95%
“…The increased rate of degradation of the collagenous matrix component to which proteoglycans are bound [21] exposes them to intraarticular proteases [22]. Progressive loss of chondrocytes, although partially compensated for by the increased metabolic activity of those remaining [23], would also contribute to the progressive decrease in cartilage proteoglycans.…”
Section: Discussionmentioning
confidence: 96%